Analisis Sentimen Masyarakat Indonesia Dalam Konflik Rusia-Ukraina Di Twitter - Muhammad Makmun Effendi; Zaenal Mustofa; Ahmad Turmudi (Bulletin of Information Technology (BIT), 2022)
Russia is a big superpower that has power and plays an important role in international politics, while Ukraine, a former Soviet Union country, became independent on December 1, 1991. In 2014 there was also a conflict between Russia and Ukraine which was a meeting of superpowers. In February 2022, Russia resumed armed conflict with Ukraine. The Russia-Ukraine conflict has garnered many responses in the form of tweets from various circles of society, resulting in many traces of tweets containing public opinion on the Russia- Ukraine conflict on Twitter social media. This study aims to determine the results of the positive or negative impact of the conflict between Russia and Ukraine on the economy in Indonesia and to determine the results of accuracy, precision, recall resulting from the use of the Naïve Bayes method and feature selection Particle Swarm Optimization in RapidMiner Studio software. Particle Swarm Optimization is an optimization method inspired by the behavior of fish and poultry flocks in search of food sources. The preprocessing stage in this research includes cleansing, removing duplicates, data selection, normalization, case folding, tokenizing, filtering, stopwords, stemming, and labeling. The classification results obtained by 55.11% of twitter users commented negatively and 44.89% of twitter users commented positively about the conflict between Russia and Ukraine. By looking at the results of the sentiment analysis data above, where the number of Twitter users who commented negatively is higher, it can be concluded that the Indonesian people are worried about the surge in prices of basic daily necessities, as indicated by one of the tweets commenting on rising oil and gas prices BBM